Pengaruh Insentif dan Kepuasan Kerja terhadap Kinerja Pegawai pada Badan Pengelolaan Keuangan dan Aset Kabupaten Lampung Utara - Jayasinga, Heylin Idelia; Yulistina, Yulistina; Windasari, Rini (Business and Enterpreneurship Journal (BEJ), 2020)
Organization is a system and human activities that work together to achieve some common goal through the division of labor and functions through responsibility. An organization requires human resources as a major supporter to achieve its intended purpose. Human Resources (HR) quality will contribute to promote a governmental organization as a container for improved performance. Â Research to be conducted kind of descriptive research, type of research is intending to make a presentation in a systematic, factual, and accurate about the facts - facts and properties - properties of a particular population. This type of research used in this research is a field (field reseach), which is a quantitative explanation is objective by explaining existing approaches. This study using 49 survey respondents. There are three variables in this study are: two (2) independent variable (X1 and X2) and 1 (one) in which the dependent variable incentives (X1) and job satisfaction (X2) as independent variables and employee performance (Y) as the dependent variable. Â From the data processing has successfully found an answer hypothesis that is as follows; Incentives are (X1) on employee performance (Y), with the level of influence (R-square) of 37.5%, which means that incentives have a relationship of 37.5% on employee performance. There is hubunugan between job satisfaction (X2) on employee performance (Y), with hubngan level of 38.2%, which means that job satisfaction empunyai relationship by 38.2% against the media results of job satisfaction. There is a relationship between incentive (X1), job satisfaction (X2) with employee performance (Y), with the level of relations of 39.7%, which means that there are incentives and belar media relations for 39.7% of the employee’s performance.